PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ARTICULATE STORYLINE PADA MATERI NILAI TEMPAT BILANGAN DUA ANGKA - Yuni Yati; Siti Aminuriyah; Siti Uswatun Khasanah; Yulia Maftuh Hidayati; Anantry Desstya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Learning mathematics in elementary schools is a subject that is mandatory for students to learn. one of the direct objectives of mathematics lessons which also plays an important role in learning is the inculcation of concepts from mathematics itself. Several previous studies have identified learning difficulties for students in understanding the place value of numbers. Therefore, mathematics learning media on two-digit value material can be developed using interactive media which will be designed and developed with the help of Articulate Storyline. The method used in this research is Research and Development (R&D) using the Borg & Gall development procedure which has been modified into 10 stages, but in this study it was only limited to stage 4. The simplification and limitation of the 10 stages to 4 steps is due to the limited manpower and time factors. The first stage is needs analysis, the second stage is Planning, Product Design Engineering, Design Validation Stage. The results obtained from the validation of material experts. The quality of the content and the purpose of the developed media get a value of 36, 80% with a feasible category. The quality of learning from the developed media gets a score of 20, a percentage of 80% with the appropriate category, the learning media that is developed is in accordance with the context of the application of the place value material for two-digit numbers. While the results of the validation from media experts stated that the technical quality of the media developed received a total score of 56, a percentage of 80% with a feasible category, the learning media developed was declared appropriate and valid for the feasibility test.